ROS production in response to high-power microwave pulses induces p53 activation and DNA damage in brain cells: Radiosensitivity and biological dosimetry evaluation - Rana, Juie Nahushkumar; Mumtaz, Sohail; Choi, Eun Ha; Han, Ihn (Frontiers in Cell and Developmental Biology, 2023)
Background: Pulsed high-power microwave (HPM) has many applications and is constantly being researched to expand its uses in the future. As the number of applications grows, the biological effects and safety level of pulsed HPM become a serious issue, requiring further research. Objective: The brain is regarded as the most vulnerable organ to radiation, raising concerns about determining an acceptable level of exposure. The effect of nanosecond pulses and the mechanisms underlying HPM on the brain has not been studied. For the first time, we observed the effect of pulsed 3.5 GHz HPM on brain normal astrocytes and cancer U87 MG cells, as well as the likely mechanisms involved. Methods: To generate 3.5 GHz HPM, an axial virtual cathode oscillator was constructed on pulsed power generator “Chundoong”. The cells were directly exposed to HPM (10, 25, 40, and 60) pulses (1 mJ/pulse), with each pulse delivered after 1 min of charging time to evaluate the dose dependent effects. Results: A strong electric field (∼23 kV/cm) of HPM irradiation primarily causes the production of reactive oxygen species (ROS), altering cell viability, mitochondrial activity, and cell death rates in U87 and astrocytes at certain dosages. The ROS generation in response to HPM exposure was primarily responsible for DNA damage and p53 activation. The hazardous dosage of 60 pulses is acknowledged as having damaging effects on brain normal cells. Interestingly, the particular 25 pulses exhibited therapeutic effects on U87 cells via p53, Bax, and Caspase-3 activation. Conclusion: HPM pulses induced apoptosis-related events such as ROS burst and increased oxidative DNA damage at higher dosages in normal cells and specific 25 pulses in cancer U87. These findings are useful to understand the physiological mechanisms driving HPM-induced cell death, as well as the safety threshold range for HPM exposure on normal cells and therapeutic effects on cancer U87. As HPM technology advances, we believe this study is timely and will benefit humanity and future research.